Analisis Kesalahan Berbahasa dalam Teks Berita Daring pada Platform Radartasik.ID 2023 - Farsya Anisa Salsabila; Fitri Nurrochmah; Wafa Luthfiah; Ai Siti Nurjamilah (Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze language errors in online news texts on the Radartasik.id platform for the December 2023 edition. Using a qualitative descriptive method, the study identifies and classifies language errors based on aspects of spelling, syntax, phonology, morphology, and semantics. Data were collected through reading and note-taking techniques, then analyzed to identify common error patterns. The results indicate various errors, including spelling, syntax, phonology, and morphology errors. The conclusions of this study are as follows: 1) Errors were found in linguistic levels, comprising 30% spelling errors, 15% syntax errors, 25% phonology errors, and 30% morphology errors. 2). Factors contributing to these frequent errors in the analysis of the news text titled Polres Tasikmalaya, TNI, and Pemkab Tasikmalaya Collaborate to Prevent and Address the Dangers of Stunting include a lack of knowledge regarding proper word usage according to KBBI (the Indonesian Dictionary) and minor issues such as lack of concentration or self-awareness during the writing process. 3) Maintaining language quality and writing standards in news texts is essential to ensure that the information conveyed by the writer is clear, accurate, and effective, as well as to uphold the media's credibility and professionalism.